2002
DOI: 10.1046/j.1523-1755.2002.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness: An early morphological marker of atherosclerotic renal disease

Abstract: These results suggest that cortical parameters are more sensitive for early diagnosis of ARD than kidney size. Cortical atrophy should be a useful marker for guidance for revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 17 publications
2
54
0
5
Order By: Relevance
“…The left RPT was greater (eg, hypertrophied column of Bertin, persistence of fetal lobation, and dromedary hump, which are usually present at the middle third portion of the left kidney), and the greatest RPT was measured on that side. This interrenal difference has been previously shown (8,9,20).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The left RPT was greater (eg, hypertrophied column of Bertin, persistence of fetal lobation, and dromedary hump, which are usually present at the middle third portion of the left kidney), and the greatest RPT was measured on that side. This interrenal difference has been previously shown (8,9,20).…”
Section: Discussionsupporting
confidence: 80%
“…A number of reports have shown that the amount of renal parenchyma decreases by about 10% per decade of advancing age for both kidneys, with the highest decrease rate in the sixth and the seventh decades independent of sex (8,9). Loss of renal parenchyma in the elderly is compensated for by an increase in peripelvic fat (9,21,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that renal cortical volume (Vc) diminishes over time in patients with chronically injured kidneys (3). Measurements of Vc may therefore be a good predictor for the progression of chronic kidney diseases, introduced as a prognostic parameter prior to renal transplantation, and may supplement measurements and investigations such as glomerular filtration rate, renographies, and biopsies.…”
Section: In Kidney Transplantation Medicine It Has Beenmentioning
confidence: 99%
“…Semiautomatic segmentation of renal cortex revealed volumetric estimations of the renal cortex ( 3 . The intraindividual and interindividual reproducibilities were Ͻ3% and Ͻ4%, respectively.…”
Section: Renal Vc Estimated By Mrimentioning
confidence: 99%